2011
DOI: 10.1371/journal.ppat.1001295
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Reactive Nitrogen Species are Barriers to Vibrio cholerae Colonization of the Infant Mouse Intestine

Abstract: Ingested Vibrio cholerae pass through the stomach and colonize the small intestines of its host. Here, we show that V. cholerae requires at least two types of DNA repair systems to efficiently compete for colonization of the infant mouse intestine. These results show that V. cholerae experiences increased DNA damage in the murine gastrointestinal tract. Agreeing with this, we show that passage through the murine gut increases the mutation frequency of V. cholerae compared to liquid culture passage. Our genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 70 publications
1
54
0
Order By: Relevance
“…As part of the microbicidal mechanism employed by macrophages, reactive oxygen species and reactive nitrogen intermediates (RNI) are excreted at very high levels, leading to DNA damage in invading organisms during infection (33,38,42,59,66). Moreover, it has been observed that pathogenic organisms such as Burkholderia spp., Brucella abortus, and Vibrio cholerae defective in DNA damage repair mechanisms are attenuated in virulence, underscoring their importance during infection (12,14,58,76). Together these findings suggest that, upon entry into the host, bacterial pathogens are faced with an array of DNA-damaging conditions.…”
Section: Discussionmentioning
confidence: 95%
“…As part of the microbicidal mechanism employed by macrophages, reactive oxygen species and reactive nitrogen intermediates (RNI) are excreted at very high levels, leading to DNA damage in invading organisms during infection (33,38,42,59,66). Moreover, it has been observed that pathogenic organisms such as Burkholderia spp., Brucella abortus, and Vibrio cholerae defective in DNA damage repair mechanisms are attenuated in virulence, underscoring their importance during infection (12,14,58,76). Together these findings suggest that, upon entry into the host, bacterial pathogens are faced with an array of DNA-damaging conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Because rifampin resistance measures base-pair substitutions in the rpoB gene and does not measure insertions or deletions (33,39,40), we developed an assay that would detect additional types of mutations in B. subtilis by scoring for trimethoprim resistance (32,41). Trimethoprim inhibits dihydrofolate reductase, thereby decreasing the concentrations of tetrahydrofolate, a critical cofactor for cellular metabolism (41).…”
Section: Resultsmentioning
confidence: 99%
“…The trimethoprim resistance assay was performed similarly to the rifampin resistance assay as described above, except that cells were grown in LB supplemented with 200 M thymidine and plated at different dilutions (32). A portion of the 10 ÏȘ6 dilution was plated on LB with 200 M thymidine, while an equal portion of the 10 ÏȘ1 dilution was plated on minimal medium plates (1% glucose 50%, 1Ï« S7 50 , 0.1% glutamate, 0.2% Casamino Acids, 0.1 M tryptophan, 0.1 M phenylalanine, 0.2 M thymidine, 34 M trimethoprim, 1Ï« metals) similar to those described previously (33) with addition of trimethoprim.…”
Section: Methodsmentioning
confidence: 99%
“…It may be that the altered virulence gene expression of the ⌬lonA mutant is detrimental when it attempts to survive and colonize the infant mouse small intestine, as it has been shown that genes in the small intestine, such as tcpA and ctxAB, are temporally and spatially regulated during infection (64). Alternatively, it may be that the in vivo fitness of the ⌬lonA mutant is compromised and that it lacks the ability to survive host defenses encountered in the infant mouse digestive tract, such as antimicrobial peptides or reactive nitrogen species (65). The inability of the ⌬lonA mutant to form a normal biofilm may also affect its ability to survive in the was used to represent expression of the T6SS.…”
Section: Discussionmentioning
confidence: 99%